2021
DOI: 10.1051/0004-6361/202040255
|View full text |Cite
|
Sign up to set email alerts
|

APOGEE discovery of a chemically atypical star disrupted from NGC 6723 and captured by the Milky Way bulge

Abstract: The central (‘bulge’) region of the Milky Way is teeming with a significant fraction of mildly metal-deficient stars with atmospheres that are strongly enriched in cyanogen (12C14N). Some of these objects, which are also known as nitrogen-enhanced stars, are hypothesised to be relics of the ancient assembly history of the Milky Way. Although the chemical similarity of nitrogen-enhanced stars to the unique chemical patterns observed in globular clusters has been observed, a direct connection between field stars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…This discovery is significant in providing unequivocal confirmation that N-rich stars born in globular clusters are lost to the field, and thus providing a bridge between both field and GC enriched populations. Recent evidence to this association has been found by Fernández-Trincado et al (2021a), who identified a chemically peculiar star just beyond the tidal radius of the bulge cluster NGC 6723. However, the optical photometry, stellar parameters, and high [C/Fe] of the star in question suggest that it may in fact be an N-normal AGB star.…”
Section: Discussionmentioning
confidence: 83%
“…This discovery is significant in providing unequivocal confirmation that N-rich stars born in globular clusters are lost to the field, and thus providing a bridge between both field and GC enriched populations. Recent evidence to this association has been found by Fernández-Trincado et al (2021a), who identified a chemically peculiar star just beyond the tidal radius of the bulge cluster NGC 6723. However, the optical photometry, stellar parameters, and high [C/Fe] of the star in question suggest that it may in fact be an N-normal AGB star.…”
Section: Discussionmentioning
confidence: 83%
“…In particular, the metal-poor stars in the field of the bulge appear to be connected to inner Galaxy GCs. Field stars with [N/Fe] overabundances are thought to be former members of a population of GCs that was previously dissolved and/or evaporated (e.g., Schiavon et al 2017;Fernández-Trincado et al 2021). This is the same mechanism that has been shown to donate stars to the halo (e.g., Martell et al 2011;Koch et al 2019).…”
Section: Introductionmentioning
confidence: 99%